Narrative fragmentation and the business cycle - Christoph Bertsch; Isaiah Hull; Xin Zhang (Sveriges Riksbank, 2021)
Using a novel rich dataset at the regional level, this paper provides new empirical evidence on the €fiscal transmission mechanism in the Eurozone. Our baseline estimates reveal a government spending relative output multiplier of 2.9, an employment multiplier of 1.9, and a cost per job created of exteuro24,000. Moreover, we €find that a regional €fiscal stimulus leads to a signi€ficant increase in private investment, productivity, durable consumption, and real wages together with a signi€ficant rise in total hours worked driven by changes in the extensive margin (total employment), whereas the intensive margin (hours per worker) barely reacts. We estimate only small regional €fiscal spillovers but detect notable state dependencies. Regional fi€scal multipliers are larger in economic recessions, during €fiscal consolidations, and in the core countries of the Eurozone.
Keywords: C63; D84; E32; E7; 330; Natural Language Processing; Machine Learning; Narrative Economics